Corrosion behaviour of an assembly between an AA1370 cable and a pure copper connector for car manufacturing applications. (1st May 2017) - Gravina, Rosanne; Pébère, Nadine; Laurino, Adrien; Blanc, Christine
Graphical abstract: Highlights: A strand and a cable made with strands do not have the same corrosion behaviour. Diffusion-controlled corrosion processes are observed for the cable. The electrolyte ingress inside cable cavities controls the corrosion processes. The higher the cavities density in assemblies, the lower the corrosion resistance. Abstract: The corrosion behaviour of an assembly between an AA1370 cable and a pure copper connector for wiring harnesses was studied in neutral chloride and sulphate containing solution. Electrochemical impedance measurements showed that the corrosion behaviour of the cable was controlled by the ingress of the electrolyte inside cable cavities. Further, local impedance measurements were performed on two assembly cross-sections, i.e. with and without cavities in the aluminium cable. The results provided evidence for both the galvanic coupling between aluminium and copper and the presence of cavities in the aluminium cable as relevant explanations for the corrosion behaviour of the assembly.